'Que yo le haré de suerte que os espante,/ si el fingimiento a la verdad excede': creative use of art in Lope de Vega's Los locos de Valencia (and Velázquez's Fábula de Aracne) - Thacker, J (Modern Humanities Research Association (MHRA), 2000)
This study makes no claim for a direct influence of Lope de Vega on Diego Velázquez, especially in the two works under consideration here: the early comedy Los locos de Valencia and the late mythological painting the Fábula de Aracne, otherwise known as Las hilanderas. Indeed, the play has been chosen not for any close similarity to Velázquez's painting but as representative, in many respects, of the early comedia in the hands of its creator. Velázquez, like any courtier or town-dweller of his day, cannot have avoided the influence of the Golden-Age comedia nueva, which was in its heyday as his career blossomed, and later frequently became, like his own painting, a deliberate (although at times ironic) expression of the grandeur of the court of Philip IV. The influence of specific Golden-Age plays on Velázquez's painting has attracted some critical attention. Of interest to me here, however, are certain parallels in the two works under consideration between the dramatist's and the painter's approaches to their art. By comparing the way painter and playwright employ art-within-art I hope to fortify some recent critics' interpretations of the Fábula de Aracne, and to reassess Lope's early play. The study dwells upon the play, which is less well known, in an attempt to show that its conceptual sophistication is comparable to that of Velázquez's painting. I shall suggest that there are two main similarities in the way art is employed by Lope and Velázquez within drama and painting, the second being arguably subsidiary to the first. Both painter and playwright use art-within-art, first to draw attention to the process, and attempt to bolster the status, of artistic endeavour in Golden-Age Spain, and secondly to express the ways in which each perceived and understood the links between art and life.